Municipal landfill leachate induces hepatotoxicity and oxidative stress in rats - Farombi, EO; Akintunde, JK; Nzute, N; Adedara, IA; Arojojoye, O (Toxicology and industrial health, 2012)
Human beings are more often exposed to complex mixtures of hazardous chemicals than single toxicant. The present study investigated the effects of Olushosun municipal landfill leachate (OMLL) from Ojota in Lagos State of Nigeria on hepatic function and some biomarkers of oxidative stress in adult rats. Physicochemical characteristic analysis of OMLL showed that while total alkalinity, total acidity, total hardness, biochemical oxygen demand and chemical oxygen demand were 3-fold, 2-fold, 4-fold and 1-fold, respectively, concentrations of heavy metals analysis showed that copper, lead, cadmium, arsenic, cobalt, chromium and mercury were 9-fold, 4-fold, 21-fold, 1320-fold, 7-fold, 5-fold and 4-fold, respectively, higher than acceptable limits by regulatory authorities. The OMLL was administered at 0, 10, 20, 30 and 40% concentrations to adult male rats for 14 days. Following exposure, serum was collected for serum biochemistry assays and liver was collected to determine the antioxidant status. Exposure of animals to 10, 20, 30 and 40% OMLL resulted in 3%, 31%, 52% and 83% increase in aspartate aminotransferase activity, whereas it elevated alanine aminotransferase activity by 10%, 25%, 30% and 49%, respectively, when compared with the control. While OMLL administration significantly increased catalase activity, a sequential decrease in reduced glutathione level and in superoxide dismutase and glutathione-S-transferase activities with concomitant increase in malondialdehyde level were observed, when compared with the control. Collectively, the hepatotoxicity of OMLL could be due to the induction of oxidative stress and may suggest possible health hazards in subjects with occupational or environmental exposure.